Simulation of stevedoring work in the Klaipeda oil terminal - Pranevičius, Henrikas; Makackas, Dalius (Transport, 2002)
The paper presents the approach of developing simulation models of stevedoring work in oil terminal using aggregate approach and simulation system ARENA. Aggregate approach permits to develop formal specification of simulated systems. Aggregate specification of the system is presented as a set of interacting piece-linear aggregates. Controlling sequences are used for formal description of each piece-linear aggregate. Transformation of aggregate formal specification to ARENA system operators permits to develop a simulation model. The developed model permits to evaluate characteristics of the Klaipeda oil terminal which are used both in queuing theory and analysing timing properties of real-time systems.First Published Online: 19 Dec 2011